A review of neonatal literature to identify critical attributes for hypothermia nursing diagnoses - Herdman, T. Heather (Rev Rene, 2013)
The aim of this study was to explore diagnostic indicators in the neonatal population for one nursing diagnosis approved by NANDA International, Inc., hypothermia, and for a proposed diagnosis, risk for hypothermia. In this integrative review, 23 articles were reviewed from the Cinahl, PubMed, and LILACS databases during the period of January through April, 2013. Data were drawn from the articles and synthesized to develop a list of potential related and/or risk factors, and defining characteristics. Potential newborn-related defining characteristics and related factors were identified for clinical testing in hypothermia, (23 and 17, respectively). Twenty-three risk factors were identified for risk for hypothermia. Diagnostic indicators for nursing diagnoses that place newborns at risk of morbidity and mortality will enable risk screening and more adequate assessments. These newly identified diagnostic indicators require research to validate their clinical usefulness.DOI:https://doi.org/10.15253/2175-6783.20130006000023